2020
DOI: 10.1016/j.bbalip.2019.158581
|View full text |Cite
|
Sign up to set email alerts
|

Conserved mechanism of phospholipid substrate recognition by the P4-ATPase Neo1 from Saccharomyces cerevisiae

Abstract: The type IV P-type ATPases (P4-ATPases) thus far characterized are lipid flippases that transport specific substrates, such as phosphatidylserine (PS) and phosphatidylethanolamine (PE), from the exofacial leaflet to the cytofacial leaflet of membranes. This transport activity generates compositional asymmetry between the two leaflets important for signal transduction, cytokinesis, vesicular transport, and host-pathogen interactions. Most P4-ATPases function as a heterodimer with a β-subunit from the Cdc50 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Although the exact substrates a P4 ATPase transport differ, the substrate translocation path appears to have been conserved in all P4 ATPase studied so far (Andersen et al, 2016;Huang et al, 2020). Like the Drs2 and ATP8A1 flippases, we found that the Dnf1 substrate translocation path is composed of TMH1-4 and TMH6 ( Fig.…”
Section: Phospholipids Bind At the Exoplasmic And Cytoplasmic Sites Omentioning
confidence: 65%
“…Although the exact substrates a P4 ATPase transport differ, the substrate translocation path appears to have been conserved in all P4 ATPase studied so far (Andersen et al, 2016;Huang et al, 2020). Like the Drs2 and ATP8A1 flippases, we found that the Dnf1 substrate translocation path is composed of TMH1-4 and TMH6 ( Fig.…”
Section: Phospholipids Bind At the Exoplasmic And Cytoplasmic Sites Omentioning
confidence: 65%
“…S4 ). Other determinants of substrate specificity, flippase activity, and exit gate position in TM2 and TM4 ( 47 , 50 , 51 ) also differ among all shown P4-ATPases (boxed residues, Fig. S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the exact substrates a P4 ATPase transport differ, the substrate translocation path appears to have been conserved in all P4 ATPase studied so far ( Andersen et al, 2016 ; Huang et al, 2020 ). Like the Drs2 and ATP8A1 flippases, we found that the Dnf1 substrate translocation path is composed of TMH1-4 and TMH6 ( Figure 3A–D , Figure 3—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%